Influence of ZnO addition on the structural, in vitro behavior and antimicrobial activity of sol–gel derived CaO–P2O5–SiO2 bioactive glasses. Issue 2 (1st February 2016) - Atkinson, I.; Anghel, E.M.; Predoana, L.; Mocioiu, O.C.; Jecu, L.; Raut, I.; Munteanu, C.; Culita, D.; Zaharescu, M.
Abstract: Bone formation, mineralization and bacterial growth control are challenging issues when developing biomedical materials. Mesoporous bioactive glasses (MBGs) in 70SiO2 –(26− x ) CaO–4P2 O5 – x ZnO ( x =0, 3 and 5 mol %) were synthesized by a sol–gel method using the non-ionic block copolymer Pluronic P123 as structure directing agent. The IV type nitrogen adsorption/desorption isotherms and pore size values between 3 and 6 nm confirmed the mesoporous structure of the synthesized MBGs. For the biological evaluation, the effect of CaO/ZnO substitution on the in vitro bioactivity of the prepared MBGs was studied by immersion in simulated body fluid (SBF) at 37 °C for 14 and 28 days, respectively. The consequent formation of the hydroxyl apatite (HA) layer and structural discrepancies of the formed layer were studied by means of appropriate techniques such as: X-ray Diffraction (XRD), Scanning Electron Microscopy (SEM), FT-IR and Raman Spectroscopy. The rate of HA precipitation followed the order 0Zn>3Zn>5Zn. The concentration of Ca, Si, P and Zn ions released from the samples into the SBF was monitored by X-ray fluorescence (XRF). High inhibition rates of 91.3% for Bacillus subtilis and respectively 89.4% for Pseudomonas aeruginosa after 2 h of incubation indicate a very good antibacterial activity of the glass with 5% ZnO.